Micro‐morphological diversity of pollen among Asteraceous taxa from Potohar Plateau‐Pakistan. Issue 7 (16th March 2022) - Usma, Anwer; Ahmad, Mushtaq; Ramadan, Mohamed Fawzy; Khan, Amir Muhammad; Zafar, Muhammad; Hamza, Mohammed; Sultana, Shazia; Yaseen, Ghulam
Abstract: Microscopic pollen characters from 19 species of family Asteraceae collected from different areas of the Potohar Plateau of Pakistan have been investigated using light and scanning electron microscopy. This study uses microscopic techniques to provide detailed information on pollen and its exine structure based on qualitative and quantitative characters. The present study has observed three types of pollen grains based on their apertures, that is, trizonocolporate, tetrazonocolporate, and tricolporate. Exine sculpturing is echinate in all studied taxa. Some species also exhibit Lacunae which differ in their shape and sizes. The size of the spines and the number of spines between the colpi play a vital role in differentiating the species of the same genus. Pollen fertility ranges from 94.3 to 74.19, showing that these species are well established in the study area. For the correct identification of species, a light and scanning electron microscopy was used that provides sufficient information for a taxonomist to distinguish species taxonomically. Research Highlights: Light and Scanning electron microscope is comparatively used to investigate the pollen characters of some species of the family Asteraceae. A scanning electron microscopy is used to study the micro‐morphological characters of pollen grains. Qualitative and quantitative characters of pollen were studied. Abstract : Light micrographs (20×) of pollen grains in polar view: (a) Ageratum conyzoides (b) Aster squamatus (c) Artemisia annua L (d) Bidens bipinnata (e) Biden psilosa (f) Causinia prolifera (g) Cirsium arvense (h) Carthamus oxyacantha (i) Erigeron canadensis (j) Erigeron bonariensis .